ANALISA KONTRIBUSI PENGALAMAN DAN LITERASI ASESMEN GURU PADA PEMBELAJARAN MASA PANDEMI COVID-19 - Muhammad Abdul Ghofur; Albrian Fiky Prakoso; Dhiah Fitrayati; Mohamad Arief Rafsanjani; Eka Hendi Andriansyah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study was to analyze the contribution of learning technology training, experience in its use, openness to change and literacy assessment of the use of online assessment in distance learning during the Covid-19 pandemic.The research method used is quantitative with the PLS-SEM statistical analysis tool. Surveys with question items that have been tested for reliability using Cronbach's Alpha with construct validation using a correlation test. The research respondents were 200 high school teachers in East Java in July 2021.The results of the study show that only the experience variable has a significant influence on the use of online assessment in the learning process. An important finding is that teachers' experience in technology-based learning is still low, even though this is the most important thing in the integration of technology in learning.